Криптосистема Рабіна на основі операції додавання - Якименко, Ігор Зіновійович; Касянчук, Михайло Миколайович; Івасьєв, Степан Володимирович (Kamianets-Podilskyi National Ivan Ohiienko University, 2019)
The paper presents the theoretical backgrounds of the Rabin's cryptosystem using only on the addition operation in virtue of reducing the time complexity of the encryption / decryption process of information flows. The proposed approach allows to increase the dimension of the input parameters to improve stability without loss of performance. An example of application of the proposed implementation of Rabin's cryptosystem is presented